2009
DOI: 10.1073/pnas.0902386106
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinking of human telomeric G-quadruplex loops by anti cyclobutane thymine dimer formation

Abstract: The unusual structural forms of telomere DNA, which protect the ends of chromosomes during replication, may render it vulnerable to unprecedented photodamage, possibly involving nonadjacent bases that are made proximate by folding. The G-quadruplex for the human telomere sequence consisting of a repeating d(T-TAGGG) is one unusual form. Tel22, d[AGGG(TTAGGG)3], forms a basket structure in the presence of Na ؉ and may form multiple equilibrating structures in the presence of K ؉ with hybrid-type structures pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 37 publications
1
71
2
Order By: Relevance
“…In addition to the spectroscopic evidence cited above supporting the assignment of an antiparallel chair structure to I 2 and a triplex structure to I 3 , the studies of Su et al [46] provide direct chemical evidence for the coexistence of chair forms as well as triplex forms for Tel22 in 150 mM KCl at 4 °C. In these studies, the authors identified the sequential positions of thymine photodimers which can only form from when proximate thymine residues are excited by UV irradiation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition to the spectroscopic evidence cited above supporting the assignment of an antiparallel chair structure to I 2 and a triplex structure to I 3 , the studies of Su et al [46] provide direct chemical evidence for the coexistence of chair forms as well as triplex forms for Tel22 in 150 mM KCl at 4 °C. In these studies, the authors identified the sequential positions of thymine photodimers which can only form from when proximate thymine residues are excited by UV irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…12) which could take place in a single step. It is noteworthy that photocrosslinking studies of Su et al [46] provide direct evidence for the presence of chair, basket and/or triple helical structures for Tel22 in K + solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of these states is however still debated. The folding pathway may include a collapse of the unfolded species into hairpin-like structures with G:G base pairs (4447), which then fold into an antiparallel G-quadruplex (37,48), then interconvert progressively into triplexes intermediates (4951) before folding properly into a G-quadruplex (37). This model is sequential, and therefore does not consider side-reactions in the mechanism, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Structural parameters have also to be taken into account, such as the nucleosome positioning that modulates the photoreactivity and therefore the ratio formation between 6-4PPs and CPDs (69). Evidence has also been provided for the enhanced efficiency of photoreactions in telomeres (70) with the possible formation of interstrand lesions in the quadruplex region (71).…”
Section: Uvb-induced Cpds and 6-4ppsmentioning
confidence: 99%